Community structure and estimation of aboveground biomass and carbon stock of beach forest in Barangay Sapao, Dumangas, Iloilo Philippines - Cordero, John Albert C. (2016.)
A beach forest is made up of creepers, shrubs, and trees above the high tide level that are adopted to grow in relatively unstable and harsh conditions. They are important in providing protection on coastal communities as exhibited by their role in the 2004 Indian Ocean tsunami and the recent onslaught of Typhoon Yolanda (Haiyan) in the Philippines. Forests naturally contain large amounts of carbon stock that help in mitigating climate change, however rampant deforestation, results in the release of carbon dioxide in the atmosphere that is hastening and magnifying the effects of climate change. This study aimed to assess the community structure and estimate the aboveground biomass and carbon stock of beach forest in Barangay Sapao, Dumangas, Iloilo. Specifically, this study aimed to identify the different beach forest species present in the area, describe the community structure (species composition, diameter at breast height and stand height, stand basal area, importance value, index of biodiversity and species richness) of the beach forest species, determine the aboveground biomass and carbon stock, and determine if there is a relationship between beach forest species diversity index and the carbon stock. The study area is in a beach forest in Barangay Sapao, Dumangas, Iloilo. Species identification was first done to identify the various beach forest species present in the site. There were three (3) 100 m transects laid down perpendicular to the shoreline with three (3) 10 m x 10 m plots at the 0-10 m, 40-50 m, and 90-100 m marks. The girth at breast height was measured 1.3 m from the ground and the tree?s height was estimated from the substrate up to the canopy in each of the sub-plots. Analysis of data for the community structure, aboveground biomass and carbon stock were done using Microsoft Excel. Overall, there were 41 beach forest species distributed among 23 families present in the site. Prosopis juliflora was the only species that occurred as very frequent (>30%), having 33% frequency of occurrence. Six species occurred as frequent (10-29%) with Caesalpinia bonduc, Cocos nucifera and Milletia pinnata having 22% frequency of occurrence while Cordia subcordata, Talipariti tiliaceum and Terminalia catappa with 11% frequency of occurrence. Barangay Sapao has a low species diversity (H?=0.76) but a high evenness index (J?=0.90). The total aboveground biomass and carbon stock were 7445.5 tons per hectare and 3350.6 tons per hectare, respectively. Cocos nucifera has the highest mean DBH (112.12 cm) which contributed to its high carbon stock (2730.7 tons per hectare). Terminalia catappa has the lowest mean DBH (11.14 cm) and the lowest carbon stock (22.8 tons per hectare). Mean DBH has a higher correlation coefficient (r=0.978) which indicates a strong positive correlation between mean DBH and carbon stock as exhibited by Cocos nucifera while mean height has a lower correlation coefficient (r=0.111) which indicates that there is a weak positive correlation with mean height and carbon stock. Management, protection and rehabilitation of beach forest is highly recommended to maximize their potential as climate change mitigators and their role in coastal protection.
Thesis -- Bachelor of Science in Biology. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Biomass -- Brgay. Sapao, Dumangas, Iloilo; Beach forest -- Brgay. Sapao, Dumangas, Iloilo; Community structure -- Beach forest -- Brgay. Sapao, Dumangas, Iloilo